Кон Noam Chomsky et Michel Foucault, Sur la nature humaine: Comprendre le pouvoir interlude: Për Noam Chomsky et Michel Foucault, Sur la nature humaine: Comprendre le pouvoir interlude - Sekulovski, Jordančo; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Jordančo Sekulovski | Јорданчо Секуловски Title (Macedonian): Кон Noam Chomsky et Michel Foucault, Sur la nature humaine: Comprendre le pouvoir interlude Title (Albanian): Për Noam Chomsky et Michel Foucault, Sur la nature humaine: Comprendre le pouvoir interlude Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 291-292 Page Count: 2 Citation (Macedonian): Јорданчо Секуловски, „Кон Noam Chomsky et Michel Foucault, Sur la nature humaine: Comprendre le pouvoir interlude“, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 291-292. Citation (Albanian): Jordančo Sekulovski, „Për Noam Chomsky et Michel Foucault, Sur la nature humaine: Comprendre le pouvoir interlude“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 291-292.